Study of the mechanism of the retarding effect by using natural gums - Palyvoda, Svetlana; Yurchak, Vera; Holikova, Tatiana; Fomenko, Venіamіn (My University, 2013)
The mechanism of natural gums' effect on the preservation of bread freshness has been studied. The stage of bread staleness was estimated from the deformation of bread’s crumb. Hydrophilicity and texture of bread crumb were also considered. The mechanism of gum’s effect on the process of bread staling was studied by determining the respective change in the state of flour starch crystal structure, which was assessed by qualitative Roentgen phase analysis and the change of bread matter moisture bonds with the addition of gums, which was determined by the method of differential thermal analysis. As the result of the research, it was found that addition of natural gums accommodates bread shelf-life extension by means of crumb texture change, as well as the effect on bread biopolymer moisture bonds
Keywords: gums; bread; freshness; structure; starch; crystallinity; moisture bonds; камеди; хлеб; свежесть; структура; крахмал; кристалличность; формы связи влаги; камеді; хліб; свіжість; крохмаль; кристалічність; форми зв’язку вологи; кафедра харчової хімії; кафедра технології хлібопекарських і кондитерських виробів; кафедра готельно-ресторанної справи